Micromeria persica Boiss. (Labiatae): A new record for Turkey - (:unkn) unknown (My University, 2007)
Micromeria persica Boiss. (Labiatae), is a new record for the Flora of Turkey in Hatay province. Illustration and description of the new species are given based on mainly examined specimens and compared with allied species.
Keywords: Micromeria persica Boiss.; New record; Turkey